Wing Simulation Using Naca 2412 and 2415 Airfoils with Variations in Angle of Attack for Lift and Drag - Medyawanti Pane (VANOS Journal of Mechanical Engineering Education, 2023)
The geometry of an airfoil plays a critical role in shaping an aircraft's performance, especially during maneuvering. This study emphasizes the necessity of conducting a comprehensive geometric analysis to better understand the effects of airfoil design. In pursuit of optimizing airfoil performance, we conducted extensive tests on NACA 2412 and 2415 series airfoil geometries using the ANSYS Fluent software. The tests employed Aluminum Alloy 1067 material and a wind speed of 300 m/s, encompassing a range of angle of attack variations from 0 to 180 degrees. The simulation results provided valuable insights into the velocity and pressure distributions surrounding the airfoil. Of particular interest, at an angle of 15 degrees, the NACA 2412 airfoil exhibited a maximum drag force of 69.670 N and a maximum lift force of 550.300 N. The corresponding drag and lift coefficients were 0,1516378 N and 1,1977364 N. For the NACA 2415 airfoil, the maximum drag and lift forces were 71.470 N and 564.500 N, respectively, with corresponding drag and lift coefficients of 0,1541963 N and 1,2179072 N.